The detection rate of human papillomavirus in well‐differentiated squamous cell carcinoma and keratoacanthoma: is there new evidence for a viral pathogenesis of keratoacanthoma?. (1st December 2019) - Conforti, C.; Paolini, F.; Venuti, A.; Dianzani, C.; Zalaudek, I.
Abstract: Linked Articles: Taibjee et al. Br J Dermatol 2019; 181 :1343–1345 ; Conforti et al. Br J Dermatol 2019; 181 :1345–1346 .